Strength and training profiles of top Greco Roman wrestlers in Finland - Vanttinen, T. (International scientific and professional conference on wrestling: "Applicable research in wrestling", 2017)
PURPOSE. The study presents strength and training profiles of five Finnish Greco Romanian wrestlers (59kg, 66kg, 75kg, 85kg, 98kg) who competed in Qualifying Tournaments for Rio de Janeiro Olympic Games held in 2016. METHODS: Athletes maximal strength (1 RM) was measured in 90° squat, bench press and power clean. Training diaries recorded with specifically developed mobile application were analyzed for 6 months before last Olympic Qualification Tournament (non qualified) or 6 months before Olympic games (qualified). RESULTS:Strength tests: squat 160 200kg (2.0 2.7 x BW), bench press 120 205kg (1.8 2.4 x BW), power clean 100 145kg (1.5 1.9 x BW). Regression analysis between maximal strength and weight category: r2 = 0.86 in squat, r2 = 0.71 in bench press and r2 = 0.77 in power clean. As an average the wrestlers practiced 10h 15min/wk (1.5h/d). The greatest number of training hours in a week was 21h (3.0h/d) during the study period. In total, training consisted of 44% wrestling, 37% strength and conditioning and 19% active recovery exercises (low intensity exercises). Wrestling sessions included 30% technique exercises, 25% matches, 16% situation battles, 15% technical and tactical matches and 13% throwing series. Strength and conditioning training included 49% endurance, 29% strength and 22% speed and explosiveness. CONCLUSION:The level of strength among Finnish top wrestlers was high (compared to athletes competing in other sports) but the strength did not discriminate those wrestlers qualified to Olympic Games (2 out of 5 wrestlers) from those who did not (3 out of 5). More variation between studied wrestlers was found on how much